Dissolution DNP NMR With Solvent Mixtures: Substrate Concentration and Radical Extraction - Harris, Talia (J Magn Reson, 2011)
Dynamic nuclear polarization (DNP) followed by sudden sample dissolution, is a topic of active investigation owing to the method’s unique prospects for the delivery of NMR spectra and images with unprecedented sensitivity. This experiment achieves hyperpolarization by the combined effects of electron-nuclear irradiation and cryogenic operation; the exploitation of these states occurs following a sudden melting and flushing of the resulting pellet from its original environment into a conventional, liquid-state setting. This melting and flushing usually demands using the equivalent of a few milliliters of hot solvent, a procedure which although well suited for in vivo studies leads to an excessive sample volume when considering typical applications within analytical settings. The present study explores a way of reducing the ensuing dilution of the hyperpolarized analytes, by employing a combination of immiscible liquids for performing the melting and flushing. It is shown that suitable combinations of immiscible solvents –both in terms of their heat capacities and densities– allow one to melt the targeted cryogenic pellet and dissolve the hyperpolarized analytes in a fraction of the solvent hitherto required. By tailoring the resulting volume to the needs of a conventional 5mm NMR probe, a substantial sensitivity enhancement can be added to the hyperpolarization process. An extra benefit may arise from using radicals that preferentially dissolve in the immiscible organic phase, by way of a lengthening of the relaxation time of the investigated analytes. Examples of these principles are given, and further potential extensions of this approach are discussed.